Design Of Food Price Analysis Dashboard In Jakarta - Salim Susanto; Dedi Trisnawarman (Jurnal Info Sains : Informatika dan Sains, 2024)
This research discusses the fluctuation of food prices in Jakarta is a complex problem and requires accurate and real-time monitoring to support decision making by the government, traders, and consumers. This research aims to design an interactive dashboard that can effectively visualize food price data and present relevant Key Performance Indicators (KPIs). The dashboard is designed by integrating various data sources such as food prices in traditional markets, inflation rates, and price comparisons between regions in Jakarta using the Time Series Analysis method. The Time Series Analysis method is used to analyze data over time, which is a set of observation values obtained at different times with the same interval. Determining key KPIs, such as daily average price, percentage price change, and monthly fluctuation trend, is the main focus in this development. The dashboard was also designed with user experience and multi-platform accessibility in mind. The result of this research is a design that can demonstrate that the dashboard can assist stakeholders in monitoring food prices more efficiently and provide critical information needed for strategic decision-making related to price stability and food policy. With intuitive visualization and real-time data, the system is expected to be an important tool in supporting food security in Jakarta.